2023
DOI: 10.1002/ppap.202300062
|View full text |Cite
|
Sign up to set email alerts
|

Warm plasma catalytic coreforming of dilute bioethanol and methane for hydrogen production

Abstract: Toward hydrogen production from renewable sources, coreforming of dilute bioethanol (5 mol% ethanol) and methane using gliding arc discharge warm plasma is reported. For warm plasma alone, increases in methane to ethanol ratio and specific energy input lead to improving hydrogen yield, but low energy efficiency (<60%). The warm plasma coupled with Ni/CeO2/Al2O3 catalyst in a heat‐insulation reactor achieves an energy efficiency of 80%, but the large axial‐temperature drop of the catalyst bed causes low conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, hydrocarbon reforming technologies by plasma-catalyst coupling such as CH 3 OH synthesis using DBD [13] and C 2 H 5 OH and CH 4 reforming using warm plasma are presented. [14] CO 2 conversion using the plasma-liquid interface is presented, [15] which is an ideal reaction system to validate the product separation concept presented in Rouwenhorst and Lefferts. [12] Plasma catalysis of CH 4 reforming is studied numerically by the chemical kinetic model of nanosecond-pulsed plasma [16] and process simulation of thermal and DBD integrated systems.…”
Section: Special Issue: Renewable Energiesmentioning
confidence: 99%
“…In addition, hydrocarbon reforming technologies by plasma-catalyst coupling such as CH 3 OH synthesis using DBD [13] and C 2 H 5 OH and CH 4 reforming using warm plasma are presented. [14] CO 2 conversion using the plasma-liquid interface is presented, [15] which is an ideal reaction system to validate the product separation concept presented in Rouwenhorst and Lefferts. [12] Plasma catalysis of CH 4 reforming is studied numerically by the chemical kinetic model of nanosecond-pulsed plasma [16] and process simulation of thermal and DBD integrated systems.…”
Section: Special Issue: Renewable Energiesmentioning
confidence: 99%
“…Moreover, these values increased as the feed gas flow rate decreased, resulting in 94% CH 4 conversion and 91% CO 2 conversion at a gas hourly space velocity (GHSV) of 3200 h -1 . In another newly reported paper, Lian et al [51] compared warm plasma coreforming of dilute bioethanol and methane to produce hydrogen, with the warm plasma-catalysis case, in which extra heating at 800 • C improved the carbon conversion from 66% to 97%, the hydrogen yield from 55% to 78% and the energy efficiency from 80% to 85%. Their research suggested the importance of extra heating in the warm plasma catalytic system, which also proves that temperature is an importance issue for post-plasma catalysis.…”
Section: Introductionmentioning
confidence: 99%